Study of cardiovascular manifestations in patients with rheumatoid arthritis - ميا, علي; عبد الله شيخ إبراهيم ,; كاسر الدو, (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Cardiovascular manifestations are considered one of the most common extra-articular manifestations of rheumatoid arthritis, and they are one of the main causes of death in these patients. Therefore, it was necessary to shed light on these manifestations for the purpose of early diagnosis and management. Research objective: To study the effects of rheumatoid arthritis on the cardiovascular system and shed light on the pathophysiological mechanisms of these manifestations. Materials and methods: A cross-sectional study that included 52 cases (43 females, 9 males) of patients with rheumatoid arthritis who were referred and admitted to the Department of Joint Diseases at Tishreen University Hospital in Lattakia during the time period 2021-2022. Laboratory evaluation of inflammatory markers (CRP and ESR),ECG with 1-minute recording strip to evaluate heart rate variability ,and transthoracic echocardiography were performed for all study patients. Results: The average age of the study patients was (51.84 ± 12.03) and the average duration of the disease was 6.5 years. The ECG was normal in 82.7% of patients. The most noticeable ECG changes in the study patients were T/ST changes in 15.3% patients, most of whom were asymptomatic. We also observed in ECG presence of QTc prolongation and decrease in heart rate variability consistent with the severity of inflammation. 42.3% of patients had a normal echocardiography, and the most common echo abnormalities seen were diastolic dysfunction at 51.9%, followed by mitral insufficiency at 23.1%, pericardial effusion at 17.3%,and aortic insufficiency at 13.5%. Conclusion: We found in patients with rheumatoid arthritis electrographic changes that included prolongation of the QT interval values, decrease in heart rate variability, and the prevalence of ischemic changes in the ST segment and the T wave. We also found by echocardiography the prevalence of diastolic dysfunction, mitral and aortic insufficiency, as well as pericardial effusion. Most of the cardiac injuries in the study patients were subclinical, and were associated with: the severity of the inflammatory activity, the age of the patient, and the duration of the rheumatoid arthritis .